2009
DOI: 10.2190/et.37.3.h
|View full text |Cite
|
Sign up to set email alerts
|

The Adjunct Advocate @ Fit: Bringing Part Time Faculty into the Mainstream

Abstract: The Adjunct Advocate @ FIT is an online, faculty development program at FIT, part of the State University of New York. This convenient new resource, developed by the Center for Excellence in Teaching, reaches out to adjunct and off-campus faculty with professional development that includes printable materials, video, discussion boards, and video-conferencing. This work-in-progress will be fully launched in spring 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…As colleges continue to strive to remain financially sound by growing student populations and campuses, it seems their budgets consistently dwindle, which includes cutbacks to full-time faculty hiring (Maldonado & Riman, 2009). More than ever, colleges are relying on contingent faculty to excel not only in teaching, but other institutional goals (Maldonado & Riman, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As colleges continue to strive to remain financially sound by growing student populations and campuses, it seems their budgets consistently dwindle, which includes cutbacks to full-time faculty hiring (Maldonado & Riman, 2009). More than ever, colleges are relying on contingent faculty to excel not only in teaching, but other institutional goals (Maldonado & Riman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More than ever, colleges are relying on contingent faculty to excel not only in teaching, but other institutional goals (Maldonado & Riman, 2009). Contingent work is defined by Labor Economists as "any job in which an individual does not have an explicit or implicit contract for long-term employment or in which the minimum hours worked can vary in a nonsystematic manner" (Umbach, 2007, p. 93).…”
Section: Introductionmentioning
confidence: 99%
“…While the percentage of faculty working part-time has hovered around 70% since 2008 (Magda, et al, 2015;Maldonado & Riman, 2009), the number of adjuncts teaching online continues to rise. A 2015 survey by The Learning House found that more than half of institutions indicated that their online adjunct population had grown over the previous year (Magda, et al, 2015).…”
Section: Adjunct Faculty Member Roles and Implicationsmentioning
confidence: 99%
“…The Fashion Institute of Technology (FIT) -another university which has relied heavily on adjunct faculty members for years -launched "The Adjunct Advocate" in Spring 2009 in order to better support part-timers (Maldonado & Riman, 2009). Developed by FIT's Center for Excellent in Teaching, this program was designed to improve student learning by connecting more part-time faculty members with teaching and learning resources.…”
Section: Participation Barriers Despite This Readiness Institutionsmentioning
confidence: 99%
See 1 more Smart Citation